(untitled) (Research, Society and Development, 2022)
The aim of this study was to assess the impact of postpartum depression (PPD) on weight retention until the sixth postpartum month. This is a longitudinal study with 563 women admitted to healthcare facilities in the city of Rio de Janeiro, between 2005 and 2009. Data were collected on weight, height, postpartum weight retention (15 days, 1st, 2nd, 4th and 6th months) and reported pregestational weight. PPD was assessed using the Edinburgh Postpartum Depression Scale, at 15 days and in the 2nd postpartum month, using 11/12 as the cutoff point. Depression was considered to be recurrent when it occurred at both times. The SAS proc mixed procedure was used for statistical analysis of the effect of PPD on postpartum weight retention. More than 30% of women started pregnancy with excess weight, 18.6% had depression at 15 days postpartum and 8.3% had recurrent depression. The analysis showed that women with recurrent PPD started to lose less weight compared to those without depression. The present study points to the importance of monitoring PPD and nutritional status, because women with recurrent depression were potentially more likely to develop overweight or obesity when they showed lesser weight loss.